The phonological neighbourhood effect on short-term memory for order - Clarkson, L; Roodenrys, S; Miller, L; Hulme, C (Taylor and Francis (Routledge), 2016)
There is a growing body of literature that suggests that long-term memory (LTM) and short-term memory (STM) structures that were once thought to be distinct are actually co-dependent, and that LTM can aid retrieval from STM. The mechanism behind this effect is commonly argued to act on item memory but not on order memory. The aim of the current study was to examine whether LTM could exert an influence on STM for order by examining an effect attributed to LTM, the phonological neighbourhood effect, in a task that reduced the requirement to retain item information. In Experiment 1, 18 participants completed a serial reconstruction task where neighbourhood density alternated within the lists. In Experiment 2, 22 participants completed a serial reconstruction task using pure lists of dense and sparse neighbourhood words. In Experiment 3, 22 participants completed a reconstruction task with both mixed and pure lists. There was a significant effect of neighbourhood density with better recall for dense than sparse neighbourhood words in pure lists but not in mixed lists. Results suggest that LTM exerts an influence prior to that proposed by many models of memory for order.